2021
DOI: 10.3390/foods10081952
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Fruits and Their Co-Products as Bioactive Compounds and Their Health Effects: A Review

Abstract: Tropical and subtropical fruits are recognized as a source of a high content of bioactive compounds and health promoting properties due to their nutritional composition. These beneficial health effects are related to the content of several of these bioactive compounds, mainly flavonoids and non-flavonoid phenolics. Many of these compounds are common in different tropical fruits, such as epicatechin in mango, pineapple, and banana, or catechin in pineapple, cocoa or avocado. Many studies of tropical fruits had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 170 publications
2
25
0
Order By: Relevance
“…Tropical fruit production and commercialisation have increased markedly, mainly in low-income areas such as Latin America and the Caribbean, with an estimated annual growth of 3.8% [ 56 ]. These fruits contain a wide variety of flavonoids, including anthocyanins.…”
Section: Sources Of Anthocyaninsmentioning
confidence: 99%
“…Tropical fruit production and commercialisation have increased markedly, mainly in low-income areas such as Latin America and the Caribbean, with an estimated annual growth of 3.8% [ 56 ]. These fruits contain a wide variety of flavonoids, including anthocyanins.…”
Section: Sources Of Anthocyaninsmentioning
confidence: 99%
“…Dietary flavonoids have been shown to interact with the microbiome [425] and the gut microbiome has emerged as a key conduit in mental health and a promising target for interventions [426][427][428]. Dietary flavones and chalcones can have important cell regulatory and tissue protective properties positively impacting on a number of diseases, many studies have shown how flavones and chalcones can impact diabetes, liver fibrosis, cancers and bacterial infections and these can also be beneficially regulated by dietary control [11,[429][430][431][432]. Pre-clinical studies have also shown that neurological disorders such as AD, PD, ALS, MS and autism can also benefit from dietary flavones and chalcones and related compounds which regulate mitochondrial activity and pathways that can generate oxidative stress.…”
Section: Bacterial Infections Associated With Long Covid Diseasementioning
confidence: 99%
“…However, combination therapy of monoclonal antibody-based immunotherapy and chemotherapeutic agents has been shown to be a promising treatment strategy for NSCLC [ 15 ]. In addition, natural flavonoids present in fruits (e.g., citrus) in combination with chemotherapeutic agents, such as cisplatin, have shown anti-NSCLC effects, demonstrated by inhibition of the α7nAChR-mediated signaling pathways involved in cellular processes including proliferation, inflammation and anti-apoptosis [ 13 , 16 ].The health benefits of fruits are due to the high levels of bioactive flavonoids they contain, such as PCs and ACNs [ 17 , 18 ]. A large number of studies have documented the health benefits of natural flavonoids derived from fruits and plant foods, in relation to their biological attributes such as anti-diabetes/anti-cancer activity, reducing cardiovascular diseases and improving the blood lipid profile [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%